2019
DOI: 10.1128/msphere.00528-19
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Dependent Dengue Virus Entry Modulates Cell Intrinsic Responses for Enhanced Infection

Abstract: Dengue is caused by infection with any one of four dengue viruses (DENV); the risk of severe disease appears to be enhanced by the cross-reactive or subneutralizing levels of antibody from a prior DENV infection. These antibodies opsonize DENV entry through the activating Fc gamma receptors (FcγR), instead of infection through canonical receptor-mediated endocytosis, to result in higher levels of DENV replication. However, whether the enhanced replication is solely due to more efficient FcγR-mediated DENV entr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 63 publications
(82 reference statements)
0
21
0
1
Order By: Relevance
“…The route of DENV entry into cells and early events of virus replication occurring thereafter are critical factors that influence the host response to infection (Flipse et al, 2013 ; Chan et al, 2019 ). As opposed to canonical dengue infections, entry of antibody-opsonized DENV during ADE is thought to occur via a phagocytosis-like pathway (Ayala-Nunez et al, 2016 ) via the cross-linking of activating FcγR present on the surface of monocytes, macrophages and dendritic cells.…”
Section: Intrinsic Ade and Antiviral Immunitymentioning
confidence: 99%
See 2 more Smart Citations
“…The route of DENV entry into cells and early events of virus replication occurring thereafter are critical factors that influence the host response to infection (Flipse et al, 2013 ; Chan et al, 2019 ). As opposed to canonical dengue infections, entry of antibody-opsonized DENV during ADE is thought to occur via a phagocytosis-like pathway (Ayala-Nunez et al, 2016 ) via the cross-linking of activating FcγR present on the surface of monocytes, macrophages and dendritic cells.…”
Section: Intrinsic Ade and Antiviral Immunitymentioning
confidence: 99%
“…This results in the dephosphorylation of spleen tyrosine kinase, a key regulator of FcγR signaling (Chan et al, 2014 ), thereby inhibiting the type1 ISG response. Yet another study by Chan et al reported the use of fluorescently labeled DENV-2 to elucidate changes in the host transcriptome as a result of both canonical receptor-mediated endocytosis and the FcγR coupled antibody mediated entry pathway (Chan et al, 2019 ). Similar viral loads were used to induce virus entry via either of these two pathways and Gene Ontology (GO) terms analysis was used to identify changes in the host transcriptome.…”
Section: Intrinsic Ade and Antiviral Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Our results of differential transcript usage or alternative splicing indicated the viral infection can cause large changes in alternative splicing of the bee hosts, which brings a new perspective on molecular mechanisms of IAPV virus pathogenesis. It is known that RNA virus can alter host mRNA splicing [57,58]. Previous research revealed that DNA methylation is linked to regulate alternative splicing in honeybees via RNA interference knocking down DNMT3 [5].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that sub-neutralizing antibodies that were cross-reactive between DENV serotypes actually increased the number of cells infected and facilitated higher virus production through a phenomenon known as antibody-dependent enhancement (ADE) ( Kou et al, 2011 ; Quinn et al, 2013 ). Mechanistically, ADE increases viral uptake into FcR-bearing macrophages ( Flipse et al, 2016 ) and also increases the expression of early host dependency factors, resulting in increased viral infection and production ( Chan et al, 2019 ). Due to the conservation of both protein sequence and structural epitopes across other flaviviruses, it has also been shown that ADE can facilitate the increased infectivity of ZIKV in individuals previously vaccinated for YFV ( Malafa et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%